Principles of the online Red Data Book development using biodiversity datasets: the Altai Mountain Country case - Shibanova, Alena; Zholnerova, Elizaveta; Zaikov, Vladimir; Sinitsyna, Tatiana; Shmakov, Alexander; Vaganov, Alexey (Zenodo, 2022)
Rare and endemic plant species could serve as a litmus test for analyzing current state of ecosystems that are rapidly changing under the anthropogenic pressure. Undisturbed foothills and mountainous areas are key places to conserve as they still retain the natural conditions as the human activity there is limited because of their difficult accessibility. We used biodiversity informatics methods for preparation of the online Red Data Book (plants) within the borders of particular natural unit – the Altai Mountain Country (AMC). The Herbarium ALTB (Barnaul) served as the empirical basis for the current study, and it is the largest plants collection from transboundary territory of the AMC and the main material of the "Flora Altaica" project. Thanks to the Herbarium ALTB digitizing, it becomes possible to identify endemics of the AMC transboundary territory and to establish the specificity of the flora without government and language barriers. Online Red Data Books created for the natural units are prospective for revealing of the endemism level and plants rarity rank. Our initial experience in the online Red Data Book development allow us to formulate some principals and approaches. The study was carried out within the framework of the State Assignments of the Ministry of Science and Higher Education of the Russian Federation No. FZMW-2020-0003. Inventory of ALTB collections and their digitizing were supported by Russian Foundation for Basic Research project No. 19-44-220004_р_а.